IMPACT OF VAT ON THE PROFITABILITY AND THE CASH FLOW OF ROMANIAN SMALL AND MEDIUM ENTREPRISES - Maria Zenovia GRIGORE; Mariana GURĂU (Challenges of the Knowledge Society)
The options available to taxpayers make tax systems attractive and give them an opportunity to choose one system or another after a careful analysis of the fiscal advantages and disadvantages of each choice. A small or medium company has to explore the options available, whether that is VAT registration or de-registration or choosing the best VAT special scheme. VAT optimisation is particularly interesting because of the high cash flow involved and because of the cash flow benefits that can be obtained. This paper presents an analysis of VAT costs and their impact on profitability and cash flow of small and medium enterprises. We also analysed specific mechanisms to improve profitability and cash flow through VAT optimisation.